Heterogeneity of social cognitive performance in autism and schizophrenia. Issue 8 (23rd April 2022) - Hajdúk, Michal; Pinkham, Amy E.; Penn, David L.; Harvey, Philip D.; Sasson, Noah J.
Abstract: Autistic adults and those with schizophrenia (SCZ) demonstrate similar levels of reduced social cognitive performance at the group level, but it is unclear whether these patterns are relatively consistent or highly variable within and between the two conditions. Seventy‐two adults with SCZ (52 male, M age = 28.2 years) and 94 with diagnoses on the autism spectrum (83 male, M age = 24.2 years) without intellectual disability completed a comprehensive social cognitive battery. Latent profile analysis identified four homogeneous subgroups that were compared on their diagnosis, independent living skills, neurocognition, and symptomatology. Two groups showed normative performance across most social cognitive tasks but were differentiated by one having significantly higher hostility and blaming biases. Autistic participants were more likely to demonstrate fully normative performance (46.8%) than participants with SCZ, whereas normative performance in SCZ was more likely to co‐occur with increased hostility and blaming biases (36.1%). Approximately 43% of participants in the full sample were classified into the remaining two groups showing low or very low performance. These participants tended to perform worse on neurocognitive tests and have lower IQ and fewer independent living skills. The prevalence of low performance on social cognitive tasks was comparable across clinical groups. However, nearly half of autistic participants demonstrated normative social cognitive performance, challenging assumptions that reduced social cognitive performance is inherent to the condition. Subgrouping also revealed a meaningful distinction between the clinical groups: participants with SCZ were more likely to demonstrate hostility biases than autistic participants, even when social cognitive performance was otherwise in the typical range. Lay Summary: Social cognition refers to the perception and interpretation of social information. Previous research has shown that both autistic people and those with schizophrenia demonstrate reduced performance on traditional social cognitive tasks, which we replicate here at the group level. However, we also found that almost half of autistic participants performed in the normal range. Over a third of participants with schizophrenia did as well, but for them this performance was accompanied by a hostility bias not commonly found in the autistic sample. Taken together, findings challenge assumptions that difficulties in social cognition are a uniform characteristic of these clinical conditions in those without intellectual disability.